MANAGEMENT OF STATUS EPILEPTICUS IN COMATOSE PATIENTS (World Science, 2021)
Among the patients with different types of Epilepsy, there is one of the most dangerous form named - Status Epilepticus, which needs emergency management. Without early response and correct treatment, patient’s health condition may become critical up to death. The most difficult treatment of Status Epilepticus is in patients with unknown coma. Under our observation, there were 22 patients with different etiological factors of coma. For clinical observation we used EEG monitoring and MRI scan in dynamics. According the health history of patients, we find out that 9 of them had immunological and unknown disorders causing Status Epilepticus. In three cases, main disease progression was determined without any leader etiological factors, which might cause immunological disorders. In 7 cases, there were nonconvulsive Status epilepticus. While all of these patients were under the general anesthesia, we were using anticonvulsive drugs in combination with immunotherapy and hormonotherapy. In two cases, we could not control Status Epilepticus. The EEG and MRI scan monitoring in dynamics shows us that difficulty in control of SE might be caused by exacerbation of the main disease. In conclusion, the acute disorders of central neuron system and early response of critical conditions are very important in correct and high quality management of both: Convulsive and non-Convulsive types of Status Epilepticus.